2015
DOI: 10.1002/2014jc010550
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of decadal variability in the Tasman Sea

Abstract: In this study, we compare optimally interpolated monthly time series Tasman Sea XBT data and a comprehensive set of ocean data assimilation models forced by atmospheric reanalysis to investigate the stability of the Tasman Sea thermocline and the transport variability of the East Australian Current (EAC), the Tasman Front, and EAC-extension. We find that anomalously weaker EAC transport at 258S corresponds to an anomalously weaker Tasman Front and anomalously stronger EAC-extension. We further show that, post … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
63
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 34 publications
11
63
1
Order By: Relevance
“…Clearly the length of the EAC time series available is relatively short, and while this application of CEOF analysis is beginning to distinguish EAC modes, a longer time series will improve the separation and important characteristics of the dominant modes. Indeed, Sloyan and O'Kane (2015), show that decadal variability in the EAC is associated with the baroclinic instability of the Pacific basin. Thus, determining and characterizing the modes of EAC variability will require a multidecadal time series.…”
Section: March 2016 S L O Y a N E T A Lmentioning
confidence: 99%
See 2 more Smart Citations
“…Clearly the length of the EAC time series available is relatively short, and while this application of CEOF analysis is beginning to distinguish EAC modes, a longer time series will improve the separation and important characteristics of the dominant modes. Indeed, Sloyan and O'Kane (2015), show that decadal variability in the EAC is associated with the baroclinic instability of the Pacific basin. Thus, determining and characterizing the modes of EAC variability will require a multidecadal time series.…”
Section: March 2016 S L O Y a N E T A Lmentioning
confidence: 99%
“…While previous work, using the available observations and ocean models, has documented long-term trends and variability of the EAC and suggested a link between the EAC variability with the large-scale Pacific Gyre forcing (e.g., Ridgway et al 2008;O'Kane et al 2011;Cetina-Heredia et al 2014;Oliver and Holbrook 2014;Sloyan and O'Kane 2015), an understanding of the fulldepth EAC property transport and its temporal variability is far from complete. What is lacking from the observational network is a sustained time series of fulldepth property observations of the boundary flow of the EAC across its entire offshore extent and of sufficient duration to resolve seasonal, interannual, and decadal signals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hill et al () found that the EAC extension and Tasman Front transport are anticorrelated in response to basin‐scale winds with a time lag of ∼3 years. Using observations and models, several other studies (Chiswell & Sutton, ; Hu et al, ; Oliver & Holbrook, ; Sloyan & O'Kane, ) have made similar findings; however, the underlying roles of nonlinear dynamics and bathymetry warrant further investigation.…”
Section: Introductionmentioning
confidence: 63%
“…This study was undertaken in the coastal‐pelagic environment adjacent to south‐eastern Australia (Figure ). The oceanography of this region is dominated by the poleward‐flowing East Australian Current (EAC), which is strengthening due to increased wind stress over a broad region of the South Pacific associated with climate change (Cai, Shi, Cowan, Bi, & Ribbe, ; Sloyan & O'Kane, ). Subsequently, south‐eastern Australia's marine environment is among the most rapidly warming regions of the global ocean (Hobday & Pecl, ).…”
Section: Methodsmentioning
confidence: 99%